CARE MOBILE “KECAMATAN HADIR UNTUK RAKYAT” PADA KECAMATAN TAKISUNG KABUPATEN TANAH LAUT - Restanto, Yudo; Estiningsih, Mudji (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2019)
The topography of Takisung Subdistrict is land, coast, mountains, hills, valleys, and streams, and has a densely populated population of 31,020 people with 9,979 family heads. The picture is a challenge for the SOPD of Takisung Subdistrict to provide the best service. As the order of the Tanah Laut Regent issued in Regent Regulation No. 60 of 2016, that subdistrict was formed in order to improve coordination of governance, public services and community empowerment. The vast subdistrict and village area and the spread of the population have caused people to be constrained in getting excellent service from the subdistrict office and village office. The elderly and disabled people have not been fully served by population services, so some do not have Identity Cards, whereas KTP is a basic requirement for obtaining social protection services. The limited number of officers possessed by the subdistrict both in terms of quantity and quality. There are 22 civil servants in the Taksiung subdistrict, while the community of Takisung subdistrict is 31,020 people. Lots of information and complaints from the community that cannot be absorbed maximally because so far the subdistrict government has only been waiting for reports from the community and the village in the office. Services carried out by the subdistrict to the community are currently only waiting at the subdistrict office, as well as guidance to the village government is only waiting at the subdistrict office.